Pelaksanaan Pembelajaran Daring pada Masa Pandemi Covid-19 di SMPN 23 Palembang - Feby Mon Harahap; Ulinniam Ulinniam; Ladestam Sitinjak; Samuel Urath; Afif Alfiyanto (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
The purpose of this study was to determine the implementation of online learning during the COVID-19 pandemic at 23 Palembang Junior High School. This research uses descriptive qualitative research, namely research methods that describe the state/object of research (a person, community institution, etc.) at the present time based on the facts that appear as they are. Data collection techniques used are observation, interviews, and documentation. The implementation of online learning can be seen from 1) providing motivation to teachers; 2) direction of the principal to teachers and staff; 3) coordination between the principal and teachers or fellow teachers; and 4) good principal communication with teachers. Factors supporting the implementation of online learning, namely 1) schools facilitate WiFi for teachers to support the online learning process while the teacher is at school; 2) teachers are able to make learning videos or find learning resources from various media; 3) provide free internet quota every month to students; 4) students are able to adapt to online learning applications, such as Google Classroom and Zoom. The inhibiting factors are 1) constrained by signal and limited internet quota; 2) unstable internet network.